[Gasherdfabrik (Spada) - Degersheim] - Gasherdfabrik (1918)
Werbeschreiben mit Unterschriftenverzeichnis (1918) [Metallindustrie/Metallbau/Apparatebau/Haushaltsgeräte/Metallverarbeitung/Haushaltstechnik/Gasherde/Gasherd/Herdfabriken/Herdfabrik/Kochherde/Kochherd Schweiz (Sankt Gallen/Kanton)]